PENGARUH KOMITMEN ORGANISASIONAL DAN KUALITAS KEHIDUPAN KERJA TERHADAP KINERJA MELALUI KEPUASAN KERJA SEBAGAI MEDIASI (Studi Pada PT. GADAR MEDIK INDONESIA) - Muhaji, 1352020002 (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aimed to investigate the effect of "Organizational Commitment And Work To Performance Through Quality of Work Life Satisfaction As Mediation (Study at PT. Gadar Medical Indonesia)" the research was sample as 134 people, using the data collected by the census technique. Data Analysis technique used is the test of the validity of the matrix component, with alfha cronbach reliabilias test, multiple regression analysis, t test and r2 with adjusted R-square. The results showed organizational commitment and significant positive effect on job satisfaction, quality of work life and significant positive effect on job satisfaction, organizational commitment and significant positive effect on performance, quality of work life is positive and significant effect on performance. Furthermore, job satisfaction organizational commitment mediates the performance and job satisfaction are also mediate on the performance quality of work life Keywords: Organizational Commitment, Quality of Work Life, Job Satisfaction and Performance